Si Pelabuhanna: Game Edukasi Pengenalan Buah-Buahan Mengandung Vitamin A menggunakan Metode Forward Chaining - Kurniawan, Rizky Rizaldi; Widiyaningtyas, Triyanna (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
Providing education in a fun way about fruits that contain vitamin A is important because one of the important benefits of vitamin A is for human vision. The purpose of this study to develop the game Si Pelabuhanna and apply the method of forward chaining to determine the eligibility of players to rise to level 2. Using the Game Development Life Cycle (GDLC) development method with stages used initiation, pre-production, production, testing, and release. Our findings are in the form of Si Pelabuhanna games that have a play menu, material, and information and apply the forward chaining method. The Si Pelabuhanna Game can be used in elementary school children's subjects where the material is about fruits containing vitamin A. Application of forward chaining method by specifying variables to be used to create rules. Rules are used to determine if a player is eligible to advance to level 2. Testing using simulation by testing one by one rule after being applied in the game. Based on the test obtained an accuracy value of 100%. This means that the forward chaining method is successfully applied to determine whether a player is eligible to rise to level 2 in a Si Pelabuhanna game.